Intermediation Spreads in a Dual Currency Economy : Argentina in the 1990s - Catao, Luis (IMF Working Papers; Working Paper ;, 1998)
The currency board arrangement and widespread dollarization of the Argentine economy since 1991 have laid the basis for domestic interest rates to converge to international levels. Although such a convergence has been observed for interest rates on bank deposits, interest rates on bank lending remain well above industrial country levels. This paper examines the causes of high intermediation spreads in Argentina using a dual currency model of the banking industry, which incorporates key features of credit markets in that country. Empirical results allow inferences to be drawn on the effects of macroeconomic and financial policies on bank lending and interest rates.